2019
DOI: 10.1590/0004-282x20190124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adapted hip-hop dancing on quality of life and social participation among children/adolescents with cerebral palsy

Abstract: To describe the influence of adapted hip-hop dancing on the quality of life (QoL) and biopsychosocial profile of children/adolescents with cerebral palsy (CP). Methods Pilot study including 18 children/adolescents with CP and Gross Motor Function Classification System levels I and II. Nine participants took part in an adapted hip-hop dance practice (study group; SG), and nine others served as the control group (CG). All participants were assessed with the Pediatric Outcomes Data Collection Instrument and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Maher et al ( 2016 ) found a positive association between physical activity, social and physical quality of life, and happiness in young people with CP. Other authors reported positive effects on QoL in children with disabilities after participating in adapted soccer and swimming (Feitosa et al, 2017 ) and in adapted hip-hop dance practice (Withers et al, 2019 ). Also interventions as an adapted cycling program had a positive effect on the emotional well-being of children with CP (Demuth et al, 2012 ; Pickering et al, 2013a , b ).…”
Section: Discussionmentioning
confidence: 98%
“…Maher et al ( 2016 ) found a positive association between physical activity, social and physical quality of life, and happiness in young people with CP. Other authors reported positive effects on QoL in children with disabilities after participating in adapted soccer and swimming (Feitosa et al, 2017 ) and in adapted hip-hop dance practice (Withers et al, 2019 ). Also interventions as an adapted cycling program had a positive effect on the emotional well-being of children with CP (Demuth et al, 2012 ; Pickering et al, 2013a , b ).…”
Section: Discussionmentioning
confidence: 98%
“…Children with neuromotor impairments often present neuromuscular alterations, deficits in postural control, and inability to perform simultaneous tasks [6,7]. Therefore, due to their health condition, children with neuromotor impairments commonly need therapeutic interventions to deal with their dysfunctions and maximize their function [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the ICF framework, rehabilitation programs directed to children and adolescents with neuromotor impairments should not only focus on the components of body structure and function, such as increases in muscle strength, range of movement, and postural stability, but also be directed to improve performance in activities of daily living and engagement in activities in home, school, and community environments [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations